Augustine's confessions - Ryken, Leland (Wheaton, Illinois : Crossway, 2015)
We’ ve all heard about the classics and assume they’ re great. Some of us have even read them on our own. But for those of us who remain a bit intimidated or simply want to get more out of our reading, Crossway’ s Christian Guides to the Classics are here to help. In these short guidebooks, popular professor, author, and literary expert Leland Ryken takes you through some of the greatest literature in history while answering your questions along the way. Each book: includes an introduction to the author and work; explains the cultural context; incorporates published criticism; defines key literary terms; contains discussion questions at the end of each unit of the text; lists resources for further study; evaluates the classic text from a Christian worldview. This volume guides readers through Augustine’ s classic spiritual autobiography, the Confessions, exploring the book’ s historical context, key themes, and overarching message.
Includes bibliographical references.
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.